Student Assessment of the E-Module for the Development of Guidance and Counseling Programs Based on Higher Order Thinking Skills in the Hybrid Learning Era - Miswanto; Zuraida Lubis; Nur Arjani; Mirza Irawan (Jurnal Amal Pendidikan, 2023)
In this era of Hybrid Learning, students need electronic modules to help understand learning materials in the course of the development of guidance and counseling programs in schools. This research aims to find out the quality of high-order thinking skills (HOTs) based electronic modules in the course of guidance and counseling program development. It is a research and development (R&D). The test subjects of this study are 20 students of the guidance and counseling study program of the Faculty of Education of Medan State University . The results of this study showed that the overall field test student assessment received an score of 81.81% with an excellent category, followed by a perceptual analysis of HOTs-based material presentation, an score of 83.30% with an excellent category, in the language aspect of 82.39% with excellent category, utilization aspect of 79.72% with good category, and graphicity aspect of 80.31% with good category. From the results of this study, the developed e-modules can already be utilized by students, especially those majoring in guidance and counseling. It is also recommended to guidance and counseling teachers/counselors to use e-modules as guidance in the development of guidance and counseling programs in schools.